Text on back: 'Frau Seger mit Tochter die von Hitler 5 1/2 Monate als Geiseln ... festgehalten wurden ...'
Text on back: 'Frau Seger mit Tochter die von Hitler 5 1/2 Monate als Geiseln ... festgehalten wurden ...'.